Evaluation of Acalypha indica extracts for antioxidant and antibacterial activities - Ruslan, Nur Fathin (2015)
For centuries, medicinal plants are being used as remedy for various ailments throughout the globe. The study was conducted emphasizing on the antibacterial and antioxidant activities of several Acalypha indica extracts. The plant was divided to leaves and stem, whole plant and roots and extracted with hexane, methanol and ethanol by successive method. Antioxidant activity was measured by 2,2-diphenyl-1- picrylhydrazyl (DPPH) Radical Scavenging assay and found to be highest in the ethanolic root extract with IC50 of 206 µg/ml. The antibacterial activity screening of different extracts was conducted by using disc diffusion, minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC) against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Enterococcus faecalis. Hexane extracts from leaves and stem, whole plant and roots showed promising results against Enterococcus faecalis with high inhibition zone at 10 to 12 mm as compared to standard antibiotics, 6 to 10 mm. All extracts showed antibacterial activity with minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values in the range from 60 to 15 mg/ml. This study concludes that A. indica explicit antioxidant and antibacterial activities may be potential for pharmaceuticals, cosmeceuticals, nutraceuticals, medical and food industry.